PROFIL LITERASI SAINS SISWA SMP DI KOTA TOMOHON PADA TOPIK PENCEMARAN LINGKUNGAN - Rizky, Muhammad; Rungkat, Jovialine A.; Rondonuwu, Anneke T. (SOSCIED, 2024)
This study aims to determine the science literacy profile of junior high school students in Tomohon City. Tomohon on the topic of environmental pollution. Descriptive with quantitative approach was the research method used in this study. The sample of this study amounted to 578 students consisting of 234 students of SMP 1 Tomohon, 169 students of SMP Negeri 3 Tomohon, 84 students of SMP Kristen Tomohon, 83 students of SMP Katolik Bunda Hati Kudus Wolouan, and 8 students of MTs. Mardhatillah Tomohon using purposive sampling technique. The research instrument used was a written test in the form of multiple choice. The results of this study showed that the science literacy profile of 578 junior high school students in Tomohon City on the topic of environmental pollution was in the range pollution is in the â€œmediumâ€ category with a percentage of 41.2%. The conclusion obtained in this study is the profile of science literacy of junior high school students in Tomohon City on the topic of environmental pollution is in the moderate category.